2018
DOI: 10.1016/j.ymgme.2018.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Necroptosis inhibition as a therapy for Niemann-Pick disease, type C1: Inhibition of RIP kinases and combination therapy with 2-hydroxypropyl-β-cyclodextrin

Abstract: Niemann-Pick disease, type C1 (NPC1) is an inborn error of metabolism that results in endolysosomal accumulation of unesterified cholesterol. Clinically, NPC1 manifests as cholestatic liver disease in the newborn or as a progressive neurogenerative condition characterized by cerebellar ataxia and cognitive decline. Currently there are no FDA approved therapies for NPC1. Thus, understanding the pathological processes that contribute to neurodegeneration will be important in both developing and testing potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 39 publications
3
23
0
Order By: Relevance
“…In stark contrast to the general lack of genotype related difference in neuronal transcriptomes, at three weeks of age, Npc1 −/− microglia already show reduced expression of linage (Tmem119) and increased expression of activation (Cd68, Igf1 and Gapdh) markers. These observations are consistent with our prior data showing corresponding changes at the protein level [27]. This observation of microglial activation preceding significant changes in neuronal transcriptome changes is consistent with the recent observation by Kavetsky et al [102] that showed increased interactions and engulfment of dendrites by microglia in the molecular layer prior to Purkinje neuron degeneration.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In stark contrast to the general lack of genotype related difference in neuronal transcriptomes, at three weeks of age, Npc1 −/− microglia already show reduced expression of linage (Tmem119) and increased expression of activation (Cd68, Igf1 and Gapdh) markers. These observations are consistent with our prior data showing corresponding changes at the protein level [27]. This observation of microglial activation preceding significant changes in neuronal transcriptome changes is consistent with the recent observation by Kavetsky et al [102] that showed increased interactions and engulfment of dendrites by microglia in the molecular layer prior to Purkinje neuron degeneration.…”
Section: Discussionsupporting
confidence: 93%
“…No significant gene expression differences were observed comparing Npc1 control and null monocytes. However, consistent with our prior work characterizing transcript levels in FACS isolated microglia [27], we observed major gene expression differences between Npc1 +/+ and Npc1 −/− microglia.…”
Section: Myeloid Transcriptomessupporting
confidence: 91%
See 2 more Smart Citations
“…In a genetic model of Niemann-Pick disease (Npc1 -/mice), RIPK1-specific inhibitor GSK′547 or transgenic overexpression of kinase-deficient RIPK1, but not Ripk3 deficiency, improved lifespan (126). These studies affirmed a RIPK3-independent role for RIPK1-dependent necroinflammation in disease pathogenesis (126).…”
Section: Necroptosis In Neurodegenerative Diseasementioning
confidence: 86%